An inward directed antenna for gastro‐intestinal radio pill tracking at 2.45 GHz. Issue 7 (7th May 2018) - Fernández, Marta; Thiel, David V.; Arrinda, Amaia; Espinosa, Hugo G.
Abstract: The accurate location of an ingested transmitter requires an array of surface electric field sensors worn on the body for more than 24 h. The small antenna (33 mm × 33 mm × 11 mm) consisting of a conductive box with a small slot (28 mm × 7 mm) pressed against the body with a centrally located feed probe was optimized to match the body impedance when located on the torso. The antenna properties when placed on different locations of the torso were calculated using computer modeling and verified using reflection measurements on 6 participants with body‐mass index between 17 and 27 kg/m 2 . Small center frequency shifts because of placing the antenna on different bodies and locations were within the 2.45 GHz bandwidth in all cases. The −10 dB bandwidth takes values between 0.75 and 0.97 GHz in simulations and between 0.51 and 1.15 GHz in measurements. The antenna design shows front‐to‐back isolation higher than 15 dB. The experimental results were not related to the body‐mass index of the participants.